The Formation Of The Image Of Conflict Situations By The Way Of Mass Media - Angelina, Demilkhanova; Oksana, Denisova (Advances in Social Sciences Research Journal, 2015)
The article is devoted to the investigations of the formation of an image of the Syrian conflict in English and Russian electronic media (for example, electronic versions of such publications as: The Guardian, The Washington Post, The New York Times, Kommersant, Izvestia, Arguments and Facts).